Report: Consultations in Education, Bridgetown, Barbados, 4 May, 1993 - CARICOM Advisory Task Force on Education (CARICOM Secretariat, 1993)
This a report of a sub-committee of the Advisory Task Force on Education on meetings held in Barbados with the Minister of Education, and with senior officials of the Ministry, as well as the representatives of regional and international agencies, and interest groups. It records the views of the participants on key education issues, concerns, and plans and programmes for the development and improvement of the Barbados education system.
A project of the CARICOM Advisory Task Force on Education in collaboration with the Ministry of Education, Barbados.
Keywords: Educational development